2001
DOI: 10.1016/s0735-1097(01)01249-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posture on cardiac autonomic nervous activity in patients with congestive heart failure

Abstract: The right lateral decubitus position in patients with CHF may be a self-protecting mechanism of attenuating the imbalance of cardiac autonomic nervous activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 18 publications
2
39
0
1
Order By: Relevance
“…10 Moreover, patients with chronic heart failure because of CAD prefer the right lateral decubitus position for significantly longer periods of time than either the left lateral decubitus or supine position, because the sympathetic nervous modulation is most attenuated in this position. 11,12 Modern medical research has found that the prone position can improve the arterial oxygen tension in acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), [13][14][15][16][17][18] and is one of the suitable positions used during general or spinal anesthesia. 19,20 ALI and ARDS are severe clinical conditions that are associated with severe oxygenation failure and very high mortality rate.…”
mentioning
confidence: 99%
“…10 Moreover, patients with chronic heart failure because of CAD prefer the right lateral decubitus position for significantly longer periods of time than either the left lateral decubitus or supine position, because the sympathetic nervous modulation is most attenuated in this position. 11,12 Modern medical research has found that the prone position can improve the arterial oxygen tension in acute lung injury (ALI) and acute respiratory distress syndrome (ARDS), [13][14][15][16][17][18] and is one of the suitable positions used during general or spinal anesthesia. 19,20 ALI and ARDS are severe clinical conditions that are associated with severe oxygenation failure and very high mortality rate.…”
mentioning
confidence: 99%
“…18,19 We consider it possible that the reason they failed to detect changes in power spectral density reflecting sympathetic or sympathovagal alterations may have been related to their failure to consider the patients' posture. Because LF/HF values in patients with CHF were shown to differ markedly among the three recumbent positions in our previous studies, 8,9 consideration of the patients' posture appears to be of great importance for analyzing HRV based on 24-h ambulatory ECG monitoring.…”
Section: Discussionmentioning
confidence: 89%
“…We previously showed that time spent in the right lateral decubitus position is significantly longer than that spent in the other recumbent positions in patients with CHF. 8,9 Therefore, the decrease in time spent in the right lateral decubitus position in these patients may itself be interpreted as a sign of improvement of CANA even without any subjective symptomatic relief.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations